Differential socioemotional and educational profiles in early childhood and primary education students in a lockdown situation - Serrano-Díaz, Noemí; Aragón, Estíbaliz; Merida-Serrano, Rosario (Frontiers in Psychology, 2024)
Recent lockdown situations have highlighted social relationship deprivation of schoolchildren and the need to develop the teaching-learning process in informal contexts. The aim of this study was to analyse differential socioemotional and educational profiles in Early Childhood and Primary Education students using variables relating to academic performance during the COVID-19 pandemic. Correlational, descriptive, and inferential statistical analyses were performed that yielded differential explanatory models depending on the stage of education. The results reveal statistically significant differences in all the variables except for family-school relationship. In the linear regression models, the most statistically significant variable for school performance in both stages was family-school relationship. However, differences were found between both profiles: emotional impact for Early Childhood Education students and social impact for Primary Education students. Lastly, leisure activities at home were included as an explanatory variable only in the Primary Education regression model. The final conclusions highlight the need to attend to the evolutionary characteristics of students in each stage to improve school performance in similar lockdown situations.